The water mite genus Procorticacarus K.O. Viets in Australasia (Acari: Hydrachnidia, Hygrobatidae) - Smit, Harry (Zootaxa, 2015)
The following new species are described: Procorticacarus curtipalpis, P. kosciuszko, P. nasutus, P. neocaledonicus, P. neoprasadi, P. paulaae, P. quadriscutatus, P. queenslandicus, P. septentrionalis and P. wenlockensis. The male of Procorticacarus australicus is described for the first time. Many new records are reported for Australia, with the first records of the genus from South Australia, Western Australia and the Northern Territory. Moreover, the genus is for the first time reported from New Caledonia. A key is given for all Australian species of the genus.